2008
DOI: 10.1089/aid.2008.0101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New CRF43_02G and CRF25_cpx in Saudi Arabia Based on Full Genome Sequence Analysis of Six HIV Type 1 Isolates

Abstract: Recently, we reported a high level of HIV-1 strain diversity in patients at the King Faisal Specialist Hospital and Research Center, Jeddah, Saudi Arabia. Based on phylogenetic analysis of gag p24, pol integrase, and env gp41 sequences, subtypes A, B, C, D, and G, and CRF02_AG, as well as unique recombinant forms were identified. Subtype G accounted for 25% of the infections in the Saudi population and this high prevalence was unexpected. Although subtype G is found in west central Africa, pure subtype G strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…1), it was weakly supported by low bootstrap estimates and by the inclusion of several CRF02 AG-derived CRFs, like CRF30 0206, 28 CRF36cpx 29 and CRF43 02G. 30 Analysis of several, recently reported Cameroonian strains assigned to CRF02 AG showed that they rather represented strains of the abovementioned variants (data not shown). Similarly, we did not find any CRF01 AE strain, although three of our strains strongly grouped with CRF22 01A1, a CRF comprising fragments of CRF01 AE.…”
Section: Discussionmentioning
confidence: 82%
“…1), it was weakly supported by low bootstrap estimates and by the inclusion of several CRF02 AG-derived CRFs, like CRF30 0206, 28 CRF36cpx 29 and CRF43 02G. 30 Analysis of several, recently reported Cameroonian strains assigned to CRF02 AG showed that they rather represented strains of the abovementioned variants (data not shown). Similarly, we did not find any CRF01 AE strain, although three of our strains strongly grouped with CRF22 01A1, a CRF comprising fragments of CRF01 AE.…”
Section: Discussionmentioning
confidence: 82%
“…CRF26_A5U and CRF45_AKU have been recently been described in samples from the DRC, 12,13 whereas CRF25_cpx and CRF37_cpx were described in neighboring Cameroon and CRF43_02G was found in Saudi Arabia. 20,21 The CRF43_02G sequence from our study clustered at a basal position of the CRF43_02G radiation suggesting a more divergent virus; characterization of other genomic regions from this sample might provide more information on the strains from Saudi Arabia and Central Africa and provide insights into the origin of this variant in Saudi Arabia. Unique recombinant pol sequences accounted for 34% of all the sequences, which is apparently in concordance with a previous study among 70 samples collected in 2002 in four provinces in the DRC and in different population groups, which reported 32.9% of recombinant pol sequences with often complex structures.…”
mentioning
confidence: 71%
“…To our knowledge, this is the first report of CRF43_02G strains in Senegal. These viruses, composed of subtype G in gag and the first part of pol, were characterized in 2008 12 and could have been missed by the first analysis on the genetic diversity in MSM, due to the absence of reference strains at that time. As some subtype G strains had been found in the MSM population group sampled in 2004, 5 these sequences were reanalyzed to determine if they belonged to the CRF43_02G clade.…”
mentioning
confidence: 99%